KPUD, PILKADA LANGSUNG DAN DEMOKRASI LOKAL - Syafriyana Hijri, Yana (Jurnal Bestari, 2008)
In the direct local head and vice local head election (Pilkada) KPUD carries out a heavy task. Its quality depens on general election implementation. In this case, KPUD is demanded to work hard, fast, and precise in supervising the direct, general, independent, confidential, honest, and fair for election. The function of KPUD is not only being general election performer but also playing leading role in local democacy process. It means that KPUD decision considerably influences democracy life. In addtion, KPUD has a strategic position, not only in leislating regulations but also in making decisions of direct local head election.Based on the main task, function, and job description, technically KPUD of Malang Regency has carried out preparation procedure of direct local head and vice local head election according to Undang-Undang No.32 Tahus 2004 which mentions that local government and some imprative stipulation established by central government.